Monitoring of Fuel Height Gauge at IoT-Based Gas Stations - Alawi, Nuril; sulistiyowati, indah (Universitas Muhammadiyah Sidoarjo, 2021)
The increasing number of motor vehicles has been increasing the fuel demands, especially the demands for ‘pertalite’ (product of fuel) and ‘pertamax’ (product of fuel) fuels. These fuels are usually placed in a cylindrical reservoir at an SPBU (gas station) that is located below the ground surface. To find out the remaining volume of BBM (fuel), gas station attendants usually check it manually by dipping the meter stick to the bottom of the reservoir. Then, the boundary surface of the fuel is used as a reference in reading the meter value. Because it was considered to be an ineffective measurement, an Android-based electronic media was created to make it easier. This tool uses the HC-SR04 ultrasonic sensor to detect the fuel height level in the reservoir. To show the results, the Blynk application is applied for the user interface. To support the IoT (internet of things) system, NodeMCU is used that is included with the WIFI module so that it can be connected to the internet. Based on the tests that have been done, the HC-SR04 ultrasound sensor has good accuracy and can monitor the height levels of fuel in real-time.